Pediatric Pain Remains Undertreated. Issue 5 (September 2021) - Beal, Judy A.
Abstract : Pain relief measures are not always used for all babies and children as necessary. Our pediatric nursing expert, Dr. Beal, explains recent evidence and current practices, then offers suggestions for neonatal and pediatric nurses to makes sure pain is treated in a timely and appropriate manner in all clinical settings.